Hebb and Cattell: The Genesis of the Theory of Fluid and Crystallized Intelligence - Brown, Richard E. (Frontiers in Human Neuroscience, 2016)
Raymond B. Cattell is credited with the development of the theory of fluid and crystallized intelligence. The genesis of this theory is, however, vague. Cattell, in different papers, stated that it was developed in 1940, 1941 or 1942. Carroll (1984, Multivariate Behavioral Research, 19, 300-306) noted the similarity of Cattell’s theory to “Hebb’s notion of two types of intelligence”, which was presented at the 1941 APA meeting, but the matter has been left at that. Correspondence between Cattell, Donald Hebb and George Humphrey of Queen’s University, Kingston, Ontario, however, indicates that Cattell adopted Hebb’s ideas of intelligence A and B and renamed them. This paper describes Hebb’s two types of intelligence, and shows how Cattell used them to develop his ideas of crystallized and fluid intelligence. Hebb and Cattell exchanged a number of letters before Cattell’s paper was rewritten in such a way that everyone was satisfied. This paper examines the work of Hebb and Cattell on intelligence, their correspondence, the development of the ideas of fluid and crystallized intelligence, and why Cattell (1943, p.179) wrote that “Hebb has independently stated very clearly what constitutes two thirds of the present theory.”